Partial and total replacement of soybean meal with urea in finishing diet for red angus X nellore growing bulls: effects on the ingestive, digestive, ruminal parameters, nitrogen balance, animal performance, and carcass characteristics - Silva, Julia Travassos da (2024)
Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES)